Terapi Komplementer Kombinasi Rendam Kaki Air Hangat dan Aromaterapi Lemon dalam Menurunkan Tekanan Darah - Siti Fadlilah; Tia Amestiasih; Bella Pebrianda; Fransiska Lanni (Faletehan Health Journal, 2021)
Combination of warm water foot soak and lemon aromatherapy has a relaxing effect to make heart beat calmer and to control blood pressure decrease. This study aims to determine the effects of the combination of warm water foot soak and lemon aromatherapy on blood pressure of prehypertensive patients in Puding Besar, Bangka Regency. The research type is a quasi-experimental study with pre-post test control group design. The samples are 32 people with prehypertension category blood pressure, taken by purposive sampling technique. The research instruments used digital sphygmomanometer, standard operating procedures for therapy and blood pressure measurement, and observational sheets. The data analysis used paired T-test and independent T-test. The mean of systole in pre-test and post-test of the control group was increased by 3.42 mmHg. The mean of diastole in pre-test and post-test of the control group was decreased by 0.18 mmHg. The mean of systole and diastole of post-test and the pre-test in the intervention group was decreased by 8.0 mmHg and 2.12 mmHg. The mean decrease of systolic and diastolic blood pressure in the intervention group was greater than the control group. The bivariate test for systole of the control and intervention group were P-values ​​of 0.041 and 0.000. The bivariate test for diastole of the control and intervention group were P-values ​​of 0.929 and 0.254. Combination therapy of warm water foot soak and lemon aromatherapy is effective to lower systolic blood pressure of prehypertensive patients.